Inventory Policy Of Medicines And Medical Equipment In Central Operation Theatre Depot Of Xyz General Hospital Bandung Using Periodic Review (r,s,s) And Joint Replenishment - Valdy Septyano; Dida Diah Damayanti; Budi Santosa (eProceedings of Engineering, 2015)
Abstract XYZ General Hospital is an A class teaching hospital which is a referral hospital that serves primary healthcare in West Java province. To serve patients, XYZ General Hospital has pharmacy warehouse which provide fifteen depots in particular ward. This research is being carried in Central Operation Theatre (COT) depot that serves central surgery ward. Central surgery ward serve major and minor operation which needs both medicine and medical equipment. To minimize cost, it is necessary to optimize inventory policy of medicines and medical equipment. ABC-VED classification was performed to determine classification of medicines and medical equipment which results are I priority and II priority category. Periodic review and joint replenishment were performed to determine R (periodic interval), s (reorder point), and S (maximum inventory) and T (periodic interval) and Q (lot size). Using proposed model, XYZ General Hospital optimize cost up to 77.75% for I priority and 79.09% for II priority. Keywords: ABC analysis, VED analysis, Hadley-Within, Periodic review (R,s,S), Joint replenishment.